Gender disparities in employment and aggregate profitability in the United States - Ajit Zacharias (Levy Economics Institute of Bard College, 2008)
We explore the relationships between aggregate profitability and women's growing share of market work in the United States during the 1980s and 1990s. Using decomposition analysis and counterfactuals, we investigate whether the contribution of the declining wage share to the upswing in profitability was aided by the growing incorporation of women into the workforce. Results show that women helped to moderate the decline in the aggregate wage share. The counterfactuals suggest that the reduction in gender pay disparity overwhelmed the negative effect of women's growing share of market work on the wage share. The decline in the wage share was driven primarily by distributional changes within the sectors rather than by changes in the composition of value added. In sectors where wage shares fell, however, women did not restrain the fall, indicating that the aggregate outcome was the net result of distinct sectoral trends in women's employment.
Keywords: B51; B54; J16; E25; 330; Feminization; Gender Inequality; Functional Distribution; Profitability